2009
DOI: 10.1159/000266204
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Paricalcitol and Calcitriol on Intestinal Calcium Absorption in Hemodialysis Patients

Abstract: Background/Aims: Increased parathyroid activity associated with chronic kidney disease is often managed with calcitriol, which can elevate serum calcium (Ca) by increasing bone resorption and intestinal absorption, whereas paricalcitol promotes less bone resorption. This study compared intestinal Ca absorption in hemodialysis patients treated with calcitriol versus paricalcitol (dose ratio 1:3). Methods: Patients (n = 22) aged ≧20 years, on maintenance hemodialysis for ≧2 months with intact parathyroid hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 49 publications
1
35
0
5
Order By: Relevance
“…Net absorption, taking into account both absorption and calcium loss, results in a net absorption of ;10% in healthy persons. In this study and previous studies of dialysis patients (27), we see percent calcium absorption values that are very low, and we see no response to vitamin D or doxercalciferol. The most probable interpretation is a defect in the mucosal response to vitamin D.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Net absorption, taking into account both absorption and calcium loss, results in a net absorption of ;10% in healthy persons. In this study and previous studies of dialysis patients (27), we see percent calcium absorption values that are very low, and we see no response to vitamin D or doxercalciferol. The most probable interpretation is a defect in the mucosal response to vitamin D.…”
Section: Discussionsupporting
confidence: 58%
“…To put this finding into perspective, healthy persons absorb ;34% of the calcium load in these conditions (23). In one older study of renal disease, calcitriol increased calcium absorption in patients with chronic renal disease on hemodialysis (9), but this effect was not reproduced in a recent study comparing calcitriol with paricalcitol (27). Although calcitriol is clearly associated with hypercalcemia in dialysis patients, it cannot be assumed this result is a result of increased calcium absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Also in chronic hemodialysis patients with SHPT paricalcitol intravenous therapy seemed to be superior compared with calcitriol therapy in a single-center randomized open label study (2). Moreover, paricalcitol has a small effect on intestinal calcium absorption compared with calcitriol in hemodialysis patients (273). were 5.4 Ϯ 1.10 to 5.9 Ϯ 1.55 mg/dl.…”
Section: Kidney Diseasementioning
confidence: 94%
“…Crossover trials of these agents in hemodialysis patients have also demonstrated less intestinal calcium absorption and less stimulation of bone resorption with paricalcitol compared with calcitriol (12,13). These differences are thought to be the result of less activation of the intestinal and bone VDRs by paricalcitol.…”
Section: Introductionmentioning
confidence: 99%